Factors influencing the participation of people with disabilities in digital skills training in Poland - Karolina Pawłowska-Cyprysiak; Katarzyna Hildt-Ciupińska; Zofia Mockałło; Sara Hamideh Kerdar (PLoS ONE, 2026)
The modern world is largely built around the use of digital technologies, which are present in life. The effective use of such technologies requires appropriate competences. People with disabilities, like everyone else, require access to digital technologies to fully participate in modern life. However, considering user diversity and the accessibility of digital technologies, digital competence training can play a key role. Therefore, the aim of this article is to present the determinants of participation in digital skills training among people with disabilities in Poland. To identify these factors, a questionnaire-based study was conducted with a group of 449 people with different disabilities. Logistic regression analysis revealed that perceived availability of accessible training significantly affects participation. When training is seen as inaccessible, the likelihood of participation decreases significantly by more than 70%. These findings highlight the need to improve the accessibility of digital skills training to ensure equal opportunities for all.